Improved oxidative stability of biodiesel via alternative processing methods using cottonseed oil. Issue 2 (4th March 2017) - Lepak, Gregory S.; Moser, Bryan R.; Bakota, Erica L.; Sharp, Julia; Thornton, C. David; Walker, Terry
Abstract: Biodiesel from waste cooking oil (WCO) requires antioxidants to meet oxidation stability specifications set forth in ASTM D6751 or EN 14214. In contrast, unrefined cottonseed oil (CSO), containing tocopherols and gossypol, produces biodiesel of higher oxidation stability. However, only a portion of these CSO endogenous antioxidants are suspected to be retained in biodiesel. Because the economics of biodiesel manufacturing rely upon inexpensive sources of triglycerides, emphasis was placed on developing improved alternative processing methods where WCO was the main source of methyl esters (WCOME) and CSO was used as a supplemental source of triglycerides and antioxidants in a 4:1 ratio. This study compared four processing methods for their ability to produce biodiesel of increased oxidative stability prepared from a 4:1 ratio of WCO:CSO. Two novel processing methods developed for this study utilise solvent properties of fatty acid methyl esters and glycerol to avoid additional chemical inventory for biodiesel processors. This study concludes that the two new processing methods resulted in biodiesel that had statistically significant improved oxidation stability when compared to two common industrial processing methods. Another significant finding is that high-shear homogenisation during transesterification reduced reaction time from the published one hour to 16 minutes.